Reading and writing/Listening and speaking (Teacher's handbook) (Oxford,New York, 2011)
This book helps students to measure their progress, with clearly stated unit objectives that motivate students to achieve their language learning goals.
Keywords: English language,Tiếng Anh; Textbooks for foreign speakers,Sách giáo khoa cho người nước ngoài